Les OGM - Un enjeu géographique majeur et un défi pour les pratiques démocratiques - Eric Glon (Territoire en Mouvement)
The European Union scenarios to promote the coexistence of GM crops and conventional or organic crops imply segregated spatial planning, an agricultural approach of the rural space and geographical areas as continuous and homogenous elements. All of these points are disputable for a geographer. So, this study aims to consider a geographical analysis of this coexistence and also how territorial populations and councils can express their opinion on this subject.